eWOM as a key factor in consumer intent to visit a destination: The moderating role of trust - Vidosavljević, Julija; Đurić, Nađa (Hotel and Tourism Management, 2025)
Purpose – Considering the intangible nature of tourism services prior to consumption, effective communication and experience exchange with other users are of critical importance. The rise in digital media usage, with the credibility of WOM communication, has led to the increasing role and significance of e-WOM in tourism. The purpose of the paper is to uncover the broader impact of e‑WOM on tourists’ decision‑making by exploring its effects on destination image and tourists’ attitudes. This study aims to examine how e-WOM, through destination image and attitude, influences the intent to visit a destination. The study also explores the moderating role of trust. Methodology – The methodology involves conducting reliability analysis, correlation analysis, and both simple and moderation regression analyses. Findings – The findings show that e-WOM positively influences tourists’ trust and attitudes, and that both trust and attitudes positively affect their intention to visit a destination. Implications – The implications of this research highlight the importance of effectively managing e-WOM, encouraging positive reviews, and addressing negative feedback in order to shape tourists’ attitudes. It highlights the importance of maintaining a strong destination image through targeted promotions and emotional connections. Trust-building through transparency and authentic communication is crucial for attracting visitors.